Long-Term Retention of Visual Tasks by Two Species of Emydid Turtles, Pseudemys nelsoni and Trachemys scripta. - Davis, Karen M.; Burghardt, Gordon M. (Journal of Comparative Psychology, 2012)
Long-lived species are expected to have long-term memory capabilities. In this study we tested nine Florida Red-bellied Cooters (Pseudemys nelsoni) on their retention for both a procedural food acquisition task and visual discrimination task learned in a previous experiment. The turtles were tested and retrained after two months, after another 7.5 months, and finally after 36 months of no interaction with the test apparatus during the intervening periods. Turtles retained memory for the choice task and needed little retraining throughout. Furthermore, in a different visual discrimination task, both P. nelsoni and Trachemys scripta turtles showed 100% retention after 3.5 months of no testing. Odor-controlled tests confirmed that turtles were using visual cues to solve the task. Thus, in a laboratory context turtles demonstrate long-term memory of visual discrimination tasks, which relates to apparent abilities in natural environments.